Stabilizing the Anionic Redox in 4.6 V LiCoO2 Cathode through Adjusting Oxygen Magnetic Moment. (12th May 2022) - Kong, Weijin; Wong, Deniz; An, Ke; Zhang, Jicheng; Chen, Zhenhua; Schulz, Christian; Xu, Zijian; Liu, Xiangfeng
Abstract: The irreversible oxygen redox and the resulting structure degradation of LiCoO2 at a high voltage cause very poor cycling performance. Herein, the anionic redox chemistry in 4.6 V LiCoO2 cathode material through manipulating the oxygen magnetic moment (OMM) with oxygen vacancy and V doping is proposed to stabilize, and the relationship between OMM and the oxidation degree of oxygen is revealed. Oxygen vacancy induces the generation of OMM, and the synergy of oxygen vacancy and V doping reduces the change of OMM during charge/discharge processes. This mitigates the oxidation degree of oxygen and improves the reversibility of oxygen redox, which greatly inhibits the irreversible oxygen escape. The oxygen vacancies can further reduce the overlap of the electron clouds and lower the O 2p band center thus decreasing the oxygen redox activity. Moreover, the introduced V also increases the energy barrier of the phase transition and suppresses the irreversible phase transition and Co migration. The irreversible O2 release is significantly inhibited and the cycling stability at 4.6 V is largely enhanced. This study presents the relationship between OMM and the oxidation degree of oxygen and provides some insights into improving the anion redox reversibility through adjusting the oxygen magnetic moment. Abstract : The anionic redox in 4.6V LiCoO2 cathode material through manipulating the oxygen magnetic moment with oxygen vacancy and V doping is proposed to stabilize, and the relationship between oxygen magnetic moment and the oxidation degree of oxygen is revealed. This mitigates the oxidation degree of oxygen and improves the reversibility of oxygen redox, which greatly inhibits the irreversible oxygen escape.